2023
DOI: 10.17159/sajs.2022/13892
|View full text |Cite
|
Sign up to set email alerts
|

Data sharing governance in sub-Saharan Africa during public health emergencies: Gaps and guidance

Abstract: While the COVID-19 pandemic has captured the attention of the global community since the end of 2019, deadly health pandemics are not new to Africa. Tuberculosis (TB), malaria and human immunodeficiency virus (HIV) count amongst other serious diseases that have had a catastrophic impact on the African continent. Effective responses to such pandemics require high-quality, comprehensive data sets that can inform policymaking and enhance healthcare decision-making. While data is driving the information economy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Indeed, bias due to consent has been reported 31. To tackle this issue in the future, data sharing governance initiatives in low-income parts of the world that aim for high-quality data collaboration, including cross-border consent, should be supported 50. In addition, we found that some publications did not provide sufficient information on the type of study being conducted; thus, misclassification of study types may have occurred.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, bias due to consent has been reported 31. To tackle this issue in the future, data sharing governance initiatives in low-income parts of the world that aim for high-quality data collaboration, including cross-border consent, should be supported 50. In addition, we found that some publications did not provide sufficient information on the type of study being conducted; thus, misclassification of study types may have occurred.…”
Section: Discussionmentioning
confidence: 94%
“…Informed consent is a legal and ethical construct used in a state-of-the-art investigation of patient data, where legal and ethical rules and regulations apply. Although legal rules vary between regions and countries, which has likely driven the differences in reporting across regions of the world, the scientific community embraces general ethical regulations globally 15–17 50. Obtaining informed consent during the COVID-19 pandemic, however, came with significant challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Brand et al do not explain why, in their view, these protections afforded by the Ghanaian DPA are "inadequate" 4 . This is a strong claim, and clearly requires more substantiation.…”
Section: Ghana's Data Protection Legislation Does Not Contain Any Pro...mentioning
confidence: 95%
“…In their recent article in this journal, Brand et al 4 add their voices to the discourse on improving data sharing governance during public health emergencies. We agree with the authors' recommendations, most pertinently the development of standard contractual clauses and data transfer agreement templates.…”
Section: Introductionmentioning
confidence: 99%
“…We thank the SAJS for affording us the opportunity to respond to a commentary 1 on our article 2 . We will focus on the principal points as raised by Thaldar et al 1 :…”
Section: Significancementioning
confidence: 99%